Effect of ingestion of soy yogurt on intestinal parameters of rats fed on a beef-based animal diet - Bedani, Raquel [UNESP] (2011)
The aim of this study was to investigate whether the ingestion of soy yogurt fermented with Enterococcus faecium CRL 183 would modify the intestinal count of enterococci, fecal pH and ammonia content in rats fed on a diet containing red meat. The rats were placed in 4 groups: for 60 days, group I was given a standard casein-based rodent feed and groups II-IV, the beef-based feed. From day 30, groups III-IV also received the following products: III) soy yogurt; IV) suspension of E. faecium CRL 183. At the start and on days 30 and 60, feces were collected for the determination of pH, ammonia content, count of enterococci and identification of their species. on day 60, rats were sacrificed and their colons also removed for count of enterococci and identification of their species. Rats that ingested soy yogurt showed no significant change (P<0.05) in fecal counts of Enterococcus spp., but, this rat group showed a higher count of E. faecium than rats that ingested suspension of E. faecium CRL 183. The ingestion of soy yogurt and E. faecium culture caused a significant rise (P < 0.05) in fecal pH and ammonia content. Our results suggest that consumption of soy yogurt fermented with E. faecium CRL 183 and L. helveticus subsp. jugurti could change the species of Enterococcus spp. present in the feces and colon of rats fed on a beef-based diet. However, the fermented soy product and the pure culture of E. faecium CRL 183 also induced undesirable effects such as the increase of fecal pH and ammonia content in the feces of rats fed on a beef-based diet.